2020
DOI: 10.3390/su12125023
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Process in the Case of Insufficient Rail Capacity

Abstract: One of the main priorities of transport policy in the EU is to take measures to support railway transport as an environmentally friendly transport mode. An interesting challenge for a railway transport operation is represented with cost items for its operation. This problem is exacerbated if transport flows are routed through a congested railway infrastructure. If some or all transport takes place on congested rail infrastructure, the carrier’s costs increase, which may ultimately lead to withdrawal from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 49 publications
(46 reference statements)
0
31
0
Order By: Relevance
“…From a technological point of view, it is important to correctly determine the technical capacity of the track section, that is, to determine the extent of train traffic for a given track section, to show sufficient stability of train traffic even during operational irregularities. The charging of capacity is one of the tools for number of train path regulation [6][7][8]. The economic aspect of capacity takes into account also the risk of paying sanctions to railway undertakings for failure to comply with the RU due to poor organization of train transport (see the introduction of the European Performance Regime (EPR) [9]).…”
Section: Requirements Of Carriers For Railway Infrastructure Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…From a technological point of view, it is important to correctly determine the technical capacity of the track section, that is, to determine the extent of train traffic for a given track section, to show sufficient stability of train traffic even during operational irregularities. The charging of capacity is one of the tools for number of train path regulation [6][7][8]. The economic aspect of capacity takes into account also the risk of paying sanctions to railway undertakings for failure to comply with the RU due to poor organization of train transport (see the introduction of the European Performance Regime (EPR) [9]).…”
Section: Requirements Of Carriers For Railway Infrastructure Capacitymentioning
confidence: 99%
“…The condition for the allocation of train paths is sufficient capacity, that is, adherence to defined conditions for ensuring the timetable quality, in particular the transportation time, with which the required buffer time (backup time) is closely related. The remaining capacity (free paths) is offered as bidding catalog paths in "ad hoc" mode to RU [1,6,11].…”
Section: New Approaches To Capacity Managementmentioning
confidence: 99%
“…In terms of economic perspective in financing large infrastructure such as railway that poises a significant investment, it has been shown that there is a polarity between the cost benefit analysis and a chunk of spillover of economic activities that may impact the society [ 24 ]. The main challenge in operating railway transport is the cost items, especially when the transport flows are routed through a congested railway infrastructure [ 25 ]. Public transport infrastructure has always deemed a reflection of the public services by which most of the Governments in the world are not looking into financial returns or simply return of investment but essentially social returns in starting the planning and development [ 26 , 27 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The purpose of these topics is, on the basis of this article, to make such analyzes of dependence, on the basis of which it is possible to improve the quality of rail transport and increase its competitiveness in the environment of a globalized society. Articles can be used for research in this direction [18] [19].…”
Section: Dependencementioning
confidence: 99%